Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2020, Creative Design Coordinator Division - Sanjaya, Lovegi David; M.Si, Agus Naryoso; M.Si, Much Yulianto; Gono, Joyo M S; Ayun, Primada Qurrota (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Public relations, as one of the strategies are quite effective for building the image, as well as long-term relationship with the community or public. This strategy is often combined with a political strategy to win a pair of political party candidates, which is the background of the writing of this scientific work ; the intention to won Irzal Ilyas and Alfauzi Bote as pair of political candidates to become mayor and deputy mayor of Solok period 2016-2021. There need to be applied various effective PR tools such as events, merchandising, advertising combined with two way communication to be established with both among the community leaders, traditional leaders and communities in Solok During the effective PR branding is applied, unique creative strategies is needed in order to create a positioning of the candidate to be accepted by the public successfuly. One of them by creating a tagline, and supporting visual design. In the progress, all of these tools will be in synergy with each other, to lead a better perception from the public about the candidate image. This “Kita Sahabat Imam” campaign has succeeded in shaping good public perception about the candidate image. although PR as one of the major contributing factors. but in the end, in the social and political world, there are always other major factors that determine the success of the elections of the candidate.